The Orthodox Church in the political system of the Russian state - Vitaly V. Penskoy, Sergey N. Borisov, Tamara I. Lipich, Pavel A. Olhov, (Opción, 2019)
This article examines the evolution of the relationship between the Russian Orthodox Church and authority in the Russian state in the early modern period via comparative qualitative research methods. As a result, the hierarchs of the Russian church had the moral right to appeal directly to the monarch and, pointing out to him that his actions did not correspond to church canons and dogmas. The authors conclude that it would be premature and unfounded to speak of the Church as internal to and dependent on the political system of the young Russian state in the early modern period.